The new paradigm of market transparency: How smartphone apps shape the markets - Gabriel-Andrei Donici; Paula-Elena Diacon (CES Working Papers, 2019)
The smartphone apps have revolutionized the markets of goods and services more than other recent technologies. Although they modified the market paradigm in sectors like accommodation, transport, or "gigs", the changes in the way the economics systems function are still widely neglected by the literature. We intend to analyze some of these changes and their impact, which in economic history could only be compared with trade liberalization. The smartphone apps increase market transparency, reduce or eliminate the entrance barriers and expand the markets to unprecedented levels. Although we limit our observations to a few cases, the apps have the potential to revolutionize any given market. For the first time since the economy has become a recognized science, market transparency is more than a utopian goal. The apps are facilitating instant information transfer between suppliers and customers. What is clear is that the increase of market transparency is not limited to the sharing economy, but it can be found in all the segments.
Keywords: 330; market transparency; pure and perfect competition; market barriers; the app economy; market vehicle